Ab Externo Choroidal Fluid Drainage, Pars Plana Vitrectomy, and Endotamponade for the Management of Persistent Hypotony following Glaucoma Surgery - Susanna Friederike Koenig; Efstathios Vounotrypidis; Christian Maximilian Wertheimer; Armin Wolf (Journal of Ophthalmology)
Background. Persistent severe serous choroidal detachment is a rare complication after glaucoma surgery. Surgical treatment with choroidal fluid drainage through a scleral incision is an option in these cases. Combining this procedure with pars plana vitrectomy and gas endotamponade has potential advantages. In the following, the perioperative course of this surgical option in a small cohort will be presented. Methods. This is a retrospective cohort study of the postoperative course of ab externo drainage of persistent serous choroidal detachment (≥4 weeks) in combination with pars plana vitrectomy and gas endotamponade in six eyes of six patients after exhausting all conservative treatment options. Inclusion criterion was persistent hypotony with severe serous choroidal detachment after intraocular pressure (IOP) lowering surgery due to medically uncontrolled glaucoma. Eyes were evaluated according to resolution of choroidal detachment, change in IOP and visual acuity (VA), postdrainage complications, and need for further surgeries. Results. Before surgery, all patients presented with flat anterior chamber, decreased vision, and persistent choroidal detachment. The surgery itself was uneventful, but due to the complexity of the cases, tailoring the procedure to each patient’s needs was required. Complete resolution of choroidal effusion was achieved by one month in 5 eyes and in 1 eye by month 3. There was an increase in average IOP from 5 (±2.1) mmHg before surgery to 11.3 (±3.7) mmHg and in VA from 1.7 (±0.8) to 1.2 (±0.6) logMAR. Five out of six patients required additional surgery, mainly to further increase the IOP even though choroidal detachment had already resolved. Conclusion. Ab externo choroidal fluid drainage combined with pars plana vitrectomy and gas endotamponade seems to be an effective and safe treatment option in persistent ocular hypotony. Although repeated surgeries might be necessary, large-scale prospective studies must be undertaken to provide corroborative evidence.